Risk of colonoscopic post-polypectomy bleeding in patients after the discontinuation of antithrombotic therapy - Kishino, Takaaki; Oyama, Tsuneo; Hotta, Kinichi; Ishii, Eiji; Momoi, Tamaki; Shimizu, Takehiro; Kunieda, Kenji; Takeda, Shinichiro; Komatsu, Hirokazu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Few studies have examined the incidence of post-polypectomy bleeding (PPB) after discontinuation of antithrombotic therapies. Therefore, this study aimed to evaluate the incidence of PPB and thromboembolic events in patients whose antithrombotic agents were discontinued before colonoscopy. Materials and Methods: We retrospectively selected all patients who underwent colon polypectomy at a community hospital. A total of 282 patients (540 polypectomies) discontinued antithrombotic agents (group 1), and 1,648 patients (2,827 polypectomies) did not take antithrombotic agents (group 2). The cessation periods before and after polypectomies were 4 and 3 days for warfarin, 5 and 3 days for anti-platelet agents, and 7 and 5 days of combination therapy, respectively. Main outcome measurements were the incidence of PPB and thromboembolic events. Results: Immediate PPB rates were 3.9% (11/282) in group 1 and 4.6% (76/1648) in group 2 (adjusted odds ratio [OR], 0.85; 95% confidence interval [CI], 0.42-1.72; p=0.65). Delayed PPB rates were 1.4% (4/282) in group 1 and 1.1% (18/1648) in group 2 (adjusted OR, 1.24; 95% CI, 0.36-4.24; p=0.732). No thromboembolic events were observed in either group. Conclusion: Our cessation periods were appropriate, and further shortening of these periods is possible.